6-Hydroxyquinolinium salts differing in the length of alkyl side-chain: synthesis and antimicrobial activity - Malinak, David; Dolezal, Rafael; Marek, Jan; Salajkova, Sarka; Soukup, Ondrej; Vejsova, Marcela; Korabecny, Jan; Honegr, Jan; Penhaker, Marek; Musilek, Kamil; Kuca, Kamil (Bioorganic & medicinal chemistry letters, 2014)
Quaternary ammonium salts substituted with a long alkyl chain exemplify a trustworthy group of medicinal compounds frequently employed as antifungal and antibacterial agents. A great asset of these surfactants underlying their widespread use is low local and system toxicity in humans. In this Letter, a series of novel quaternary 6-hydroxyquinolinium salts with varying length of N-alkyl chain (from C10 to C18) was synthesized and tested for in vitro activity against pathogenic bacterial and fungal strains. 6-Hydroxyquinolinium salt with C12 alkyl chain seems to be very interesting candidate due to a high antimicrobial efficacy and cytotoxic safety.
Keywords: CHO buňky; antiinfekční látky; Quaternary Ammonium Compounds; Fungi; Salts; křečci praví; Cricetinae; LC–MS; zvířata; grampozitivní bakterie; Gram-Negative Bacteria; Cricetulus; chinolinové sloučeniny; Microbial Sensitivity Tests; houby; mikrobiální testy citlivosti; soli; Surfactants; Antimicrobial activity; kvartérní amoniové sloučeniny; Cell Survival; viabilita buněk; CHO Cells; 6-Hydroxyquinolinium salts; Anti-Infective Agents; Synthesis; gramnegativní bakterie; Animals; Gram-Positive Bacteria; Quinolinium Compounds